2020
DOI: 10.1039/c9sm01973a
|View full text |Cite
|
Sign up to set email alerts
|

Poroelasticity of (bio)polymer networks during compression: theory and experiment

Abstract: Soft living tissues like cartilage can be considered as biphasic materials comprised of a fibrous complex biopolymer network and a viscous background liquid. Here, we show by a combination of experiment and theoretical analysis that both the hydraulic permeability and the elastic properties of (bio)polymer networks can be determined with simple ramp compression experiments in a commercial rheometer. In our approximate closed-form solution of the poroelastic equations of motion, we find the normal force respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“…Finite difference techniques were used to solve the resulting partial differential equations and this gave results that were in qualitative agreement with experiments. In doing so, we have gone beyond analytically solvable problems that require assumptions of small strains [21], but have stopped short of writing a fully three-dimensional continuum theory for the compression of fibrous gels. A fully three-dimensional continuum calculation can be done using finite elements, but not without significant effort in developing appropriate elements to handle poro-elasticity with large deformations and phase transitions.…”
Section: Resultsmentioning
confidence: 99%
“…Finite difference techniques were used to solve the resulting partial differential equations and this gave results that were in qualitative agreement with experiments. In doing so, we have gone beyond analytically solvable problems that require assumptions of small strains [21], but have stopped short of writing a fully three-dimensional continuum theory for the compression of fibrous gels. A fully three-dimensional continuum calculation can be done using finite elements, but not without significant effort in developing appropriate elements to handle poro-elasticity with large deformations and phase transitions.…”
Section: Resultsmentioning
confidence: 99%
“…We presented a new technique for the measurement of Poisson's ratio of micrometric soft hydrogels with a very good measurement accuracy. The absolute measurement errors varying from 0.002 to 0.012 are comparable to what is obtainable using X-ray diffraction [12], and are much smaller than for measurements relying on the determination of two independent elastic moduli [7,30]. We successfully used this approach to measure Poisson's ratios of different hydrogels and showed that this Poisson ratio varied in a large range of values (0.165 to 0.5).…”
Section: Discussionmentioning
confidence: 84%
“…To make this calculation, membrane permeability was measured empirically, as described below. Meanwhile, tissue permeability, which is known to be influenced by the degree of tissue strain ( Holmes, 1985 ; Punter et al ., 2020 ), was approximated from an equation describing the relationship between the deformation and permeability of bovine NP tissue ( Heneghan and Riche 2008a ), This equation defines tissue permeability in terms of the stretch ratio, λ = h f / h o where h o denotes the initial height of the specimen and h f denotes the final height after confined compression. For the current study, pressure was applied isotropically to the tissue; therefore, it was assumed that tissue compression proceeded radially.…”
Section: Methodsmentioning
confidence: 99%